International monetary cooperation - Halm, George N. (Chapel Hill : University of North Carolina Press, 1945)
This book is an attempt to explain the importance of International Monetary Fund and review the discussions which led to the Agreement of Bretton Woods.
Includes index
Bibliographical foot-notes.
usc 27/04/18
Loans
Keywords: Currency question; Foreign exchange